Turing Machine / Nordin Abu Bakar (Universiti Teknologi MARA, Terengganu, 1992)
Turing Machine is one of the earliest device in programming to describe or interpret a model for algorithmic specification. Beside Turing, Church and Kleene also offer their own formulations to define computability of functions. This article will take a glance through some formulations of computability by some Turing machines and their support to Church's Thesis.